2009
DOI: 10.1007/s10803-009-0834-0
|View full text |Cite
|
Sign up to set email alerts
|

ABA Versus TEACCH: The Case for Defining and Validating Comprehensive Treatment Models in Autism

Abstract: The authors analyzed the results of a social validation survey to determine if autism service providers including special education teachers, parents, and administrators demonstrate a preference for the intervention components of Applied Behavior Analysis or Training and Education of Autistic and other Communication Handicapped Children. They also investigated the comprehensiveness of these treatment models for use in public school programs. The findings indicate no clear preference for either model, but a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 31 publications
0
31
0
9
Order By: Relevance
“…22 Behavioral management techniques used in Pediatric Dentistry can be applied to patients with ASD. These techniques are divided in two groups, basic and advanced techniques, according to the same contraindications considered for children without ASD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…22 Behavioral management techniques used in Pediatric Dentistry can be applied to patients with ASD. These techniques are divided in two groups, basic and advanced techniques, according to the same contraindications considered for children without ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Body stimuli and sound stimuli (words and sounds) can also be used in this method, which is aimed mainly to patients with poor verbal communication. 22,23 Tsang et al 23 concluded that children subjected to treatment with TEACCH showed a significant improvement of their motor skills and perception capacity. ABA ABA is the acronym for Applied Behavior Analysis.…”
Section: Requires Great Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Actualmente, las terapias que cuentan con mayor validez debido a su eficacia clínica en el espectro autista, son la terapia ABA (Applied Behavioral Analysis, Leaf y McEachin, 1998;Trivisonno, 2007) y la terapia TEACCH (Treatment and Education of Autistic related Communication Handicapped Children) (Mesibov y Howley, 2003;Mesibov, Shea y Schopler, 2006;Callahan, Shukla-Mehta, Magee, y Wie, 2010;Virués-Ortega, 2010).…”
Section: Terapias Actuales Para El Espectro Autistaunclassified